2019
DOI: 10.1158/1078-0432.ccr-18-2984
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Validity of HPV Circulating Tumor DNA in Advanced Anal Carcinoma: An Ancillary Study to the Epitopes-HPV02 Trial

Abstract: Purpose: Human papillomavirus (HPV) is found in 90% of squamous cell carcinomas of the anal canal (SCCA). We investigated the clinical validity of HPV circulating tumor DNA (ctDNA) detection in patients enrolled in the Epitopes-HPV02 trial that demonstrated the efficacy of docetaxel, cisplatin, and 5-FU as first-line chemotherapy in advanced SCCA.Experimental Design: According to the protocol, serum samples were collected before chemotherapy and on completion of chemotherapy. HPV16 ctDNA was quantified by drop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 26 publications
3
83
0
Order By: Relevance
“…Circulating tumor DNAs (ctDNAs) are mutated gene fragments that are exclusively shed by cancer cells into blood, 7 which can be detected by digital polymerase chain reaction (dPCR) 8 or sequencing. In patients with metastatic breast cancer, ctDNA by dPCR was reported to outperform classic tumor biomarker (CA15-3/CEA) and circulating tumor cells in monitoring disease progression 9 as well as identifying resistant clonal evolution during therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating tumor DNAs (ctDNAs) are mutated gene fragments that are exclusively shed by cancer cells into blood, 7 which can be detected by digital polymerase chain reaction (dPCR) 8 or sequencing. In patients with metastatic breast cancer, ctDNA by dPCR was reported to outperform classic tumor biomarker (CA15-3/CEA) and circulating tumor cells in monitoring disease progression 9 as well as identifying resistant clonal evolution during therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the Epitopes-HPV02 trial, HPV ctDNA was detected at baseline in 91% of patients. After treatment with DCF, residual HPV ctDNA was present in 39% of patients and was highly predictive of disease progression (HR = 5.5; p < 0.001) and OS (HR = 7.0; p = 0.02) [11], validating the interest of HPV ctDNA in routine clinical practice in advanced SCCA patients [12].…”
Section: Introductionmentioning
confidence: 76%
“…10 Centre Antoine-Lacassagne, Nice, France. 11 Hôpital Européen Georges-Pompidou, Paris, France. 12 Centre Hospitalier Universitaire de Bordeaux, Bordeaux, France.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The use of cf-DNA for the detection of circulating HPV-DNA has been investigated in a number of other studies and cancer types, with reported detection sensitivities that are similar to our findings (91%). In different HPV-induced malignancies, detection sensitivities of cf-DNA analyses have been reported to range from 86%-100% in anal SCC (n = 19 and n = 57), cervical SCC (n = 33), and head and neck SCC (n = 93, including oral cavity, oropharynx, hypopharynx and larynx subsites) [22][23][24][25] . For HPV-OPCSCC specifically, three studies have demonstrated detection sensitivities of 95.6% (n = 97), 89% (n = 103), and 88.5% (n = 114) [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%